Horace: l’âme et son destin - Setaioli, Aldo (Cuadernos de Filología Clásica. Estudios Latinos, 2006)
In Horace we find only scattered hints, from which it is not easy to draw a consistent conception of the soul. It is clear, however, that he does not grant the soul any self-standing status in relation to the body. Horace is sceptical concerning doctrines which grant the soul the capability to transcend the body’s limitations, and even more concerning those that promise immortality, including metempsychosis. A tragic feeling of death fills a great part of his poetry. Only in the consolatory ode addressed to Virgil (c. 1, 24, 19-20) does he propose manly acceptance of the inevitable, which elsewhere he tries to exorcize through wine and pleasure. For Horace the afterworld is a mood much more than a definite place. Mythological and poetical references to the next life are not lacking, but the picture which prevails in his poetry is the desolate one found in Homer’s poems. With this pessimistic view Horace does not refrain from contradicting even his friend Virgil. Not even songs more beautiful than Orpheus’s can bring the dead back to life. The one remedy is resignation, as proposed in the ode to his fellow poet.